Determination Levels of Tumor Necrosis Factor Receptor and Tolk like Receptor -4 and bacterial vaginosis in women with Recurrent Spontaneous Abortion - Sumaya Yahya Abed Obais; Shaimaa Jassim Alsultany (Institute of Medico-legal Publications Pvt Ltd, 2021)
The presents study included Determination levels of Tumor necrosis factor and Tolk like receptor -4 inwomen with recurrent spontaneous abortion in province of Babylon, 100 samples were collected, whereas50 samples with recurrent abortion women and 50 healthy women as control groups ,the results of presentsstudy shown that the concentration of tumor necrosis factor receptor in serum of women with recurrentabortion and control was showed significantly differences between control and cases (P? 0.044), the Meanof tumor necrosis factor receptor (TNFR) in serum of patients women with recurrent abortion was 52.08 pg/ml,Whereas in control, the concentration of tumor necrosis factor receptor in serum of healthy women was42.77 pg/ml.Tolk like receptor 4 concentration in serum of women with recurrent abortion and control was significantlydifferences between cases and control (P ? 0.001), the mean of Tolk like receptor 4 concentration in serumof women with recurrent abortion was 3.95 pg/ml While In serum of women without abortion (control), themean of Tolk like receptors 4 was 2.84 pg/ml.The results of statistical analysis shown that the tolk like receptor-4 marker that is significantly differences at( p ? 0.05 ) positive correlation with age (r = .698**) , and its positively correlation with abortion (r= .505*) ,the tumor necrosis factor receptor was significantly differences at ( p ? 0.05) and positively correlation withage and the value of r was reached to .539*and its positive correlation with abortion ( r =.854**)